Generating photocurrent by nanocomposites based on photosynthetic reaction centre protein. Issue 11 (23rd September 2015) - Szabó, Tibor; Nyerki, Emil; Tóth, Tünde; Csekő, Richárd; Magyar, Melinda; Horváth, Endre; Hernádi, Klára; Endrődi, Balázs; Visy, Csaba; Forró, László; Nagy, László
Abstract : An optoelectronic device, which converts light energy to electric potential, was designed and fabricated by using photosynthetic reaction centre (RC) proteins of purple bacterium Rhodobacter sphaeroides R‐26, based on the structure and function of the dye sensitised organic solar cells. First, an electrochemical cell with three electrodes was created especially for this measurement. ITO covered by the MWCNT‐RC containing sample served as the working electrode and the counter and the reference electrodes were platinum and Ag\AgCl, respectively. Water soluble ubiquinone‐0 and ferrocene, in some experiments were used as mediators. In another experiment, the presence of the RCs in the active layer under dried conditions assured tuneable wavelength sensitivity, in general in the visible, but specially, in the near infrared (700–1000 nm) spectral range. The lifetime of the primary charge separation is in the ps time scale and that of the charge stabilisation can be modulated (at least theoretically) between ps and seconds. A successful combination of RC protein with a light energy converter device in spectroelectrochemical cell (wet conditions in buffered electrolyte) and in dried multilayer structure will be presented here.